Semaphorin7A promotes tumor growth and exerts a pro-angiogenic effect in macrophages of mammary tumor-bearing mice - Garcia-Areas, Ramon; Libreros, Stephania; Amat, Samantha; Keating, Patricia; Carrio, Roberto; Robinson, Philip; Blieden, Clifford R.; Iragavarapu-Charyulu, Vijaya (Frontiers in Physiology, 2014)
Semaphorins, a large family of molecules involved in the axonal guidance and development of the nervous system, have been recently shown to have both angiogenic and anti-angiogenic properties. Specifically, semaphorin 7A (SEMA7A) has been reported to have a chemotactic activity in neurogenesis, and to be an immune modulator via it binding to α1β1integrins. Additionally, SEMA7A has been shown to promote chemotaxis of monocytes, inducing them to produce proinflammatory mediators. In this study we explored the role of SEMA7A in the tumoral context. We show that SEMA7A is highly expressed by DA-3 murine mammary tumor cells in comparison to normal mammary cells (EpH4), and that peritoneal macrophages from mammary tumor-bearing mice also express SEMA7A at higher levels compared to peritoneal macrophages derived from normal control mice. We also show that murine macrophages treated with recombinant murine SEMA7A significantly increased their expression of proangiogenic molecules, such as CXCL2/MIP-2. Gene silencing of SEMA7A in peritoneal elicited macrophages from DA-3 tumor-bearing mice resulted in decreased CXCL2 expression. Mice implanted with SEMA7A silenced tumor cells showed decreased angiogenesis in the tumors compared to the wild type tumors. Furthermore, peritoneal elicited macrophages from mice bearing SEMA7A-silenced tumors produce significantly (p< 0.01) lower levels of angiogenic proteins, such as MIP-2, CXCL1 and MMP-9, compared to macrophages from control DA-3 mammary tumors. We postulate that SEMA7A derived from mammary carcinomas may serve as a monocyte chemoattractant and skew monocytes into a pro-tumorigenic phenotype. A putative relationship between tumor-derived SEMA7A and monocytes could prove valuable in establishing new research avenues towards unraveling important tumor-host immune interactions in breast cancer patients.